2015
DOI: 10.1002/cncr.29351
|View full text |Cite
|
Sign up to set email alerts
|

Religion/spirituality and health in the context of cancer: Cross‐domain integration, unresolved issues, and future directions

Abstract: This article summarizes the findings of 3 previous meta‐analytic reviews presented in this issue that evaluate associations between religiousness/spirituality (R/S) and patient‐reported outcomes across mental, physical, and social health domains. The results are synthesized, caveats in interpreting this set of analyses are discussed, directions are provided for future research, and tentative suggestions are made for clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
(30 reference statements)
1
31
0
1
Order By: Relevance
“…Recent meta-analyses of 1341 effects drawn from over 44,000 patients with cancer demonstrated an overall positive relationship between RS and self-reported measures of health outcomes (Park et al, 2015) but the strength of that relationship varied as a function of both the RS dimension and the physical (Jim et al, 2015), mental (Salsman et al, 2015), and social (Sherman et al, 2015) outcomes assessed. The strongest relationships were found between affective dimensions of RS (e.g., sense of meaning, purpose, or connection to a source larger than oneself) and mental health outcomes, whereas behavioral RS constructs (e.g., service attendance, prayer and meditation) showed few significant associations with health, except for a modest positive relationship with social health outcomes.…”
Section: Rs and Health Research: Current Findings And Critiquementioning
confidence: 99%
See 1 more Smart Citation
“…Recent meta-analyses of 1341 effects drawn from over 44,000 patients with cancer demonstrated an overall positive relationship between RS and self-reported measures of health outcomes (Park et al, 2015) but the strength of that relationship varied as a function of both the RS dimension and the physical (Jim et al, 2015), mental (Salsman et al, 2015), and social (Sherman et al, 2015) outcomes assessed. The strongest relationships were found between affective dimensions of RS (e.g., sense of meaning, purpose, or connection to a source larger than oneself) and mental health outcomes, whereas behavioral RS constructs (e.g., service attendance, prayer and meditation) showed few significant associations with health, except for a modest positive relationship with social health outcomes.…”
Section: Rs and Health Research: Current Findings And Critiquementioning
confidence: 99%
“…However, further study of the two factor structure indicated that the meaning/peace component was too closely related to anxiety and that separating this instrument into three domains–meaning, peace, and faith–provides more informative constructs and better psychometric properties (Peterman et al, 2014). In addition to moving away from a two factor model of the FACIT-Sp, care should be taken to avoid using the measure as a predictor of well-being outcomes—a common misuse which confounds predictor and outcome variables (Park et al, 2015). …”
Section: Future Directions Anticipated Barriers and Research Recommmentioning
confidence: 99%
“…thirdly, the awareness on how religion and spirituality influence cancer adaptation is scarce. In this sense, there are still very few studies examining how different concepts of death, disease and transcendence influence cancer-coping in both, family and the patients [10] .…”
mentioning
confidence: 99%
“…Using this approach, the degree to which the overall relation between affective measures of R/S and mental health outcomes is inflated by spiritual well-being measures could be more clearly delineated. We also discussed this problem in our commentary [1]. …”
mentioning
confidence: 99%
“…Given space constraints, we could include only a limited number of sub-analyses and thus we chose to focus on providing a broad overview of the findings for R/S and mental health relationships as well as a more nuanced summary of these relationships as a function of type of R/S dimension, type of mental health outcome, and potential moderating variables. We acknowledged the need for greater attention to selection of psychometrically strong R/S measures in the accompanying commentary [1]. …”
mentioning
confidence: 99%